DEVELOPMENT OF ANDROID-BASED PETA (PENJELAJAHAN MATEMATIKA) LEARNING MEDIA ON SPEED LEARNING MATERIALS AT A FIFTH-GRADE ELEMENTARY SCHOOL - Salsabila Baliani Putri Sopian; I. Isrokatun; Ali Ismail (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
This paper describes the developmental process of PETA (Penjelajahan Matematika)learning media based on the Android application on speed learning materials at a fifth-gradeelementary school, determines the feasibility of the application through the validation process ofexperts, and finds out the compatibility of applications in several devices with different Androidversions. The research uses a research and Development (RnD) method with the ADDIE model(Analysis, Design, Development, Implementation, Evaluation). The results of the research are (1) thedevelopment of the PETA application is relevant to the needs of the mathematics learning process onspeed learning material at class V SD, (2) the design of the PETA application is adopted from theconcept of exploring games with various forms of presentation, (3) the PETA application design thathas been made is developed into file.apk., (4) the PETA application has the feasibility of the content inthe very feasible category with a percentage of 97%, the feasibility of the media in the very feasiblecategory with a percentage of 92.75%, and already fulfilled the standard of portability on adaptabilityand installability aspects with a testing percentage of 100%, and (5) the final product of the PETAapplication is developed based on the evaluation results at the testing stage of functional suitabilityand portability by making minor improvements to the instruction aspects of the use and the additionalmenu of an